Innovativeness of Polish enterprises in the initial period of system transformation - Baruk, Jerzy (Technovation)
The author examines innovativeness in Polish industry since the transformation of its economy to a market-based one. It appears that the changes commenced in 1989 did not influence innovation in any evident way.